2007
DOI: 10.1111/j.1365-3024.2007.00987.x
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition–parasite interactions in goats: is immunoregulation involved in the control of gastrointestinal nematodes?

Abstract: Compared to sheep, goats seem to develop a low immune response against the parasitic nematodes of the gastrointestinal tract. Nevertheless, some variability in the host response has been observed either at the individual level or depending on internal (genetic) or external (physiological status, nutrition) factors suggesting the possibility to exploit and manipulate this response. There is good evidence from field studies to suggest that a better plane of nutrition might contribute to improve goat resilience. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
1
4

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 79 publications
(139 reference statements)
4
73
1
4
Order By: Relevance
“…This contradicts some previous studies that found a lower prevalence in goats (Kanyari et al, 2009;Khan et al, 2010;Abebe et al, 2011), but is in agreement with a number of other studies, which also reported higher parasite prevalence in goats (Regassa et al, 2006;Nwosu et al, 2007;Gadahi et al, 2009;Dagnachew et al, 2011). Hoste et al (2008) suggested that goats do not develop resistance as efficiently as sheep and this may be an explanation for our findings.…”
Section: Discussionsupporting
confidence: 63%
“…This contradicts some previous studies that found a lower prevalence in goats (Kanyari et al, 2009;Khan et al, 2010;Abebe et al, 2011), but is in agreement with a number of other studies, which also reported higher parasite prevalence in goats (Regassa et al, 2006;Nwosu et al, 2007;Gadahi et al, 2009;Dagnachew et al, 2011). Hoste et al (2008) suggested that goats do not develop resistance as efficiently as sheep and this may be an explanation for our findings.…”
Section: Discussionsupporting
confidence: 63%
“…Native sheep of tropical regions possibly have innate resistance against GIN, which can interfere with the benefits of supplementation on resistance against GIN in growing animals. This phenomenon is less common in animals of less resistant species or breeds (Torres-Acosta et al, 2004;Hoste et al, 2008). The selection of grazing/browsing stratum was similar between experimental groups and was maintained constant throughout the trial.…”
Section: Effect On Resilience or Resistance Against Gin Infectionmentioning
confidence: 99%
“…Seasonal fluctuations in availability (wet v. dry season) -E-mail: ccastro@uady.mx and the diverse chemical composition of the forages available for sheep feeding affect the nutrient supply for growth and production (Romano-Muñ oz et al, 1983;Pfister and Malechek, 1986). The role of strategic supplementation as an alternative tool in the control of GIN in small ruminants under semi-intensive systems has been studied in recent years (Knox et al, 2006;Hoste et al, 2008;Torres-Acosta and Hoste, 2008). Infections with GIN can alter the host's feed intake, the nutrient partition (Adams and Liu, 2003;Colditz, 2008) and possibly the metabolism of the host.…”
Section: Introductionmentioning
confidence: 99%
“…Gastrointestinal parasitism constitutes one of the main constraints to the outdoor and extensive breeding of goats in temperate and tropical countries (HOSTE et al, 2005(HOSTE et al, , 2008COELHO et al, 2012). For years, it has been considered that data obtained on parasite infections in sheep could be directly transferred to goats (HOSTE et al, 2010), and thus disregarding specific studies on goat parasitism and its consequences.…”
Section: Introductionmentioning
confidence: 99%